Exploring the patterns and antecedents of charitable giving among Muslim community in Malaysia - Awang, Salwa Amirah; Borhan, Joni Tamkin; Mohamad, Mohamad Taqiuddin; Muhammad, Fidlizan (Online Journal of Research in Islamic Studies, 2015)
This article aims to explore the trends and determinants of charitable giving among Muslim community in Malaysia due to its importance in the economy as the income redistribution tool to improve the welfare of the society. The Theory of Planned Behaviour is employed to predict the giving intention of 248 respondents in the state of Selangor. The result of the findings shows that the trends of giving among the respondents and using the multiple regression analysis, it indicates that this theory is able to predict the charitable giving behaviour by 70% and that the attitude and perceived behavioural control are the significant influential factors to the giving intention. This study contributes empirically for Islamic charity marketers to improve their fundraising strategies so that they will be able to function in improving the well-being of the society.